USING DICTOGLOSS TO TEACH THE ENGLISH HYPOTHETICAL CONDITIONAL CONSTRUCTION: AN EXPERIMENTAL SUPPORT - Angeria Verawati (Indonesian JELT, 2015)
The current study reports on an investigation into the effects ofusing dictogloss to teach the English hypothetical conditionalconstruction. Twenty four Indonesian EFL learners (initiallyfifty) studying English as a compulsory subject at a localsecondary school in Jakarta participated in an instructionaltreatment that is called dictogloss. An interpretation task and aproduction task were used in the pretest and posttest in this studyto measure the learners’ performance after the treatment. Thefindings revealed positive effects on both learners’ interpretationand production abilities. The participants improved significantlyin their abilities to comprehend and use the target construction.One reasonable pedagogical implication is that dictogloss is aneffective language teaching method, and should be used ifteachers want to vary their teaching techniques.Keywords: dictogloss, Indonesian EFL learners, theEnglish hypothetical conditional construction,pedagogical implications